Efficacy of the P-POSSUM scoring system as a prognostic indicator in patients undergoing emergency laparotomy - Anbarasu, Karthic; Chandak, Rohit (International Surgery Journal, 2019)
Background: Continuous audit of surgical practice is essential in enhancing patient care and lowering health care cost. This prospective study aimed to assess the validity of the Portsmouth- physiologic and operative severity score for the enumeration of mortality and morbidity (P-POSSUM) score in predicting the risk of morbidity and mortality and to identify the risk factors for poor outcome at a tertiary care teaching hospital in India. Methods: A prospective study of 100 patients (70 emergency and 30 elective) undergoing exploratory laparotomy admitted in Department of General Surgery over a 10 months period at Rabindranath Tagore Medical College, Udaipur, Rajasthan, were included in the study group. The risks of mortality and morbidity were calculated by using P-POSSUM equation. The predicted risks were compared with the observed risks of mortality and morbidity and statistically analysed. Results: The overall mortality rate of 11% with (O:E=0.85, p=0.59) and morbidity rate of 41% with (O:E=0.78, p=0.089). Higher percentage of mortality and morbidity were found with patients not able to be resuscitated successfully before surgery. Chest infections (18%), pyrexia (15%) and wound infections (14%) are areas requiring prompt care to minimize mortality rate. Conclusions: Even though P-POSSUM over predicted mortality it was not statistically significant as concluded by other studies. With P-POSSUM outcome of the patient and operative risk can be predicted and pre-operative counselling, optimization, implementing resuscitative measures and adequate care in specific high risk groups can be given with targeted interventions; improving quality of care and cost reduction.